On the Gorenstein locus of simplicial affine semigroup rings. Issue 9 (2nd September 2022) - Jafari, Raheleh; Taherizadeh, Abdoljavad; Yaghmaei, Marjan
Abstract: We study the Gorenstein locus of simplicial affine semigroup rings in terms of some Apéry sets. The results come from an analysis of Cohen-Macaulay type of homogeneous localizations at monomial prime ideals. Characterizing when the homogeneous localization at a monomial prime ideal is Gorenstein, we can read the dimension of the non-Gorenstein locus. In particular, we determine when the semigroup ring is Gorenstein on the punctured spectrum.